A Comparative Study of Bioinformatics Skills of Pre-service Biology Teachers with and without a Bioinformatics Course - Sari, Indah Juwita; El Islami, R. Ahmad Zaky; Maida, Citra; Yustika, Diana; Santoso, Muhammad Iman (Journal of Applied Science, Engineering, Technology, and Education, 2026)
The rapid growth of bioinformatics has significantly influenced both the biological sciences and education, underscoring the importance of equipping future biology educators with relevant analytical and computational skills. This study aimed to compare the bioinformatics skills and biological knowledge of biology education students with and without experience in bioinformatics courses. A comparative descriptive design was employed, involving 49 students: 26 with no prior experience in bioinformatics and 23 with experience in bioinformatics. Data were collected using an instrument consisting of three opinion-based items and three cognitive test items. Qualitative data were analyzed thematically and visualized through diagrams, while cognitive performance was analyzed using descriptive statistics. The outcomes show that students who took the bioinformatics course demonstrated a broader use of tools, more reflective thinking about their own learning, and encountered more difficult problems, along with greater gain in scores on biology knowledge (70.29%) compared to students who did not take the course (63.63%). These findings support the need to include bioinformatics in the biology education program to better prepare pre-service biology teachers with the science and technology advancements in the future